The best part - Page,Tommy; Amy Mastura; PonyCanyon Entertainment (Malaysia). (Kuala Lumpur : PonyCanyon Entertainment, 1996)
Terdapat tiga buah lagu berirama pop yang terdapat dalam album ini.
CD 1 : The Best Part -- The Best Part (karaoke version) -- My Heart Keeps On Calling Your Name.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English